DECREASED BRAINSTEM AND PUTAMEN SERT BINDING POTENTIAL IN DEPRESSED SUICIDE ATTEMPTERS USING [11C]‐ZIENT PET IMAGING. Issue 10 (22nd March 2013) - Nye, Jonathon A.; Purselle, David; Plisson, Christophe; Voll, Ronald J.; Stehouwer, Jeffrey S.; Votaw, John R.; Kilts, Clinton D.; Goodman, Mark M.; Nemeroff, Charles B.
<x xml:space="preserve">Abstract</x> Background Deficits in serotonergic neurotransmission have been implicated in the pathogenesis of depression and suicidality. The present study utilized a novel positron‐emission tomography (PET) ligand to quantitate and compare brain regional serotonin transporter (SERT) binding potential in depressed patients with a past history of suicide attempts to that of healthy comparison subjects. Method We used [11C]‐ZIENT PET to label SERT in the serotonergic cell body rich brainstem, and forebrain projection fields. Quantitative PET emission data from 21 adults (10 healthy controls and 11 drug‐free patients with major depression) was used for group comparison. SERT binding potential (BPND) in eight MRI‐based brain regions of interest (ROI) were compared in high‐resolution PET images. Results SERT binding potential was significantly decreased in the midbrain/pons (P = .029) and putamen (P = .04) of depressed patients with a past suicide attempt relative to comparison subjects. Forebrain SERT binding was also reduced in the patient sample, though these region effects did not survive a multiple comparison correction. Conclusion These results suggest that decreased availability of the brainstem and basal ganglia SERT represents a biomarker of depression and thus confirm and extend the role of dysregulation of brain serotonergic neurotransmission in the pathophysiology of depression and suicide.